A Qualitative Study on the Lived Experiences of Women with Polycystic Ovary Syndrome Attending Gynecology OPD, Bangalore - Pitti Meghasandhya; S. Padmaja (International Journal of Midwifery Nursing And Practices, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent hormonal disorder among women of reproductive age, affecting multiple aspects of their well-being, including physical, psychological, emotional, social, and spiritual dimensions. Despite its widespread occurrence, the lived experiences of women with PCOS remain inadequately understood. The present qualitative study aimed to explore and interpret these lived experiences to enhance professional awareness, improve understanding, and promote better support for affected women. A phenomenological research design using Interpretative Phenomenological Analysis (IPA) was employed. Purposive sampling was used to recruit participants until data saturation was achieved. A total of 21 women aged 18–30 years with a diagnosis of PCOS participated in semi-structured interviews guided by open-ended questions. Interviews were audio-recorded, transcribed verbatim, and coded. The data were analyzed to identify significant statements, which were organized into thematic clusters and overarching themes. The analysis revealed four major themes: physical; psychological and emotional; social; and spiritual experiences. Subthemes included weight concerns, hair and skin problems, menstrual irregularities, sleep disturbances, mood swings, anxiety about infertility, low self-esteem, social isolation, and feelings of divine punishment. The study highlights the profound impact of PCOS across various dimensions of women’s lives and underscores the importance of holistic, empathetic, and individualized care. In conclusion, women with PCOS experience multifaceted challenges that affect their quality of life. These findings emphasize the need for greater professional recognition, targeted health education, and supportive interventions to enhance coping, understanding, and access to comprehensive care.
Keywords: Polycystic ovary syndrome (PCOS); interpretative phenomenological analysis (IPA); lived experiences; phenomenological study; women’s health